Control of photovoltaic‐based low‐voltage dc microgrid system for power sharing with modified droop algorithm. Issue 6 (1st May 2016) - Augustine, Sijo; Lakshminarasamma, N.; Mishra, Mahesh Kumar
Abstract : This study discusses a droop‐based proportional load sharing control of parallel connected dc–dc converters in photovoltaic (PV)‐based low‐voltage dc microgrid. Droop control is the popular scheme for power sharing in dc microgrid. In this study, proportional droop index (PDI) algorithm with droop ( R droop ) shifting is introduced to improve the load sharing performance of the dc microgrid, which is a function of normalised current sharing difference and voltage deviation in the output side of the converters. This proposed control method calculates adaptive virtual resistance, R droop, and allows the converter to share the load current based on PV power available. By incorporating a new R droop shifting method with PDI, the proposed scheme eliminates the trade‐off between current sharing and voltage regulation of the conventional method. The detailed analysis and design procedures are explained, and the effectiveness of the proposed method is verified by detailed simulation and experimental studies.